The effect of credit scoring on small business lending in low- and moderate-income areas - W. Scott Frame; Michael Padhi; Lynn Woosley (Federal Reserve Bank of Atlanta, 2001)
This paper empirically examines the effect of the use of credit scoring by large banking organizations on small business lending in low- and moderate-income (LMI) areas. Using census tract level data for the southeastern United States, the authors estimate that credit scoring increases small business lending by 16.4 million per LMI area served. Furthermore, this effect is almost 2.5 times larger than that estimated for higher income census tracts (6.8 million). The authors also find that credit scoring increases the probability that a large banking organization will make small business loans in a given census tract. The change in this probability is 3.8 percent for LMI areas and 1.7 percent for higher income areas. These findings suggest that credit scoring reduces asymmetric information problems for borrowers and lenders and that this is particularly important for LMI areas, which lenders may have historically bypassed because of their questionable economic health.
Keywords: 330; Credit scoring systems; Bank loans; Commercial loans; Small business